2015
DOI: 10.1111/fcp.12116
|View full text |Cite
|
Sign up to set email alerts
|

Impact of recommendations on crushing medications in geriatrics: from prescription to administration

Abstract: The practice of crushing drugs is very common in geriatric units. In 2009 a first study, performed in all geriatric units of a university hospital, showed that numerous errors were made during prescription, preparation and administration. The aim of this second prospective study was to assess the impact of regional and national recommendations in the same geriatric units. A survey of 719 patients (85.3 ± 6.7 years) was performed in 2013. For each patient who received crushed drugs, we recorded the reason the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 16 publications
2
41
0
Order By: Relevance
“…In accordance with previous literature (Bourdenet et al, 2015;Stubbs et al, 2008), medicines affecting the CNS were modified most frequently, followed by drugs acting on the Cardiovascular System, which indicates that these commonly prescribed medication classes, do not meet the needs of older patients and further research investigating this is necessary.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In accordance with previous literature (Bourdenet et al, 2015;Stubbs et al, 2008), medicines affecting the CNS were modified most frequently, followed by drugs acting on the Cardiovascular System, which indicates that these commonly prescribed medication classes, do not meet the needs of older patients and further research investigating this is necessary.…”
Section: Discussionsupporting
confidence: 83%
“…pharmacokinetic and pharmacodynamic changes (Mc Gillicuddy et al, 2015;Stegemann et al, 2010;Stegemann et al, 2012). Other studies have found that modifications may also arise due to the culture within the institution including prescribing, dispensing and administration practices and communication and multi-disciplinary team engagement (Bourdenet et al, 2015;Hanssens et al, 2006;Kelly et al, 2011a). Alternatives to ODF modification recommended in the best practice guidelines include unlicensed formulations or alternative medicines (Wright et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that crushing could have been avoided in nearly half of the patients who received their tablets crushed because they swallowed the placebos without having difficulties during laryngoscopy. This appears particularly relevant because crushing was inadequate in about 20 % of all modified drugs (alarmingly, this seems to be rather common as reported by other authors [18,42,43]), and therefore patients were put at an increased risk of overdosage or treatment failure. Furthermore, all of these drugs could have been either suspended instead of being crushed or replaced by pharmaceutically or therapeutically equivalent dosage forms for which crushing or suspending is permitted.…”
Section: Discussionmentioning
confidence: 91%
“…After implementation of system improvements, there was reduction of nonconformities to 70%, especially regarding the crushing of enteric coated pills. They also found that, after utilizing the good practice Thus, it was observed that recommendations of the guide contributed to improvements in the care practice of elderly patients (Goedecke et al, 2016) (Bourdenet et al, 2015).…”
Section: Discussionmentioning
confidence: 98%